The effectiveness of employees’ representative organisations in Zimbabwean parastatals: a case of Grain Marketing Board. - Sithole, Amanda T. (Midlands State University, 2017)
This study investigates the effectiveness of employees’ representative organisations in Zimbabwean parastatals. A case study of Grain Marketing Board was used. The study seeks to examine if employees in Zimbabwean parastatals, looking at the case of GMB, are being fully represented. The study goes into detail trying to fill the gap looking at what has been causing continuous poor representation in these parastatals. The study used both qualitative and quantitative research. The study focused on non-managerial employees. All the employees that were under investigation viewed that the Grain Marketing Board Workers Union was biased towards management. Some stated that the law of Zimbabwe is now out ruling the necessity of these organisations due to the retrenchments that had been taking place. More so, the study viewed that these employees noticed that poor education amongst representatives as another cause of ineffective and inefficient representation by the GMBWU. The study also gives recommendations. The study recommends that these representatives should go for some training to enhance their representative skills. A further investigation on the effectiveness of employees’ representation in Zimbabwean parastatals should be carried out.